EKOSISTEM LAMUN DAN MAKROZOOBENTHOS DI TAMAN NASIONAL KEPULAUAN SERIBU - Tegas Gentur Sosiawan; Tatang Mitra Setia; Sakdullah (TECHNO-FISH, 2022)
The higher anthropogenic activities in the Thousand Islands National Park, especially in residential islands, will affect seagrass ecosystems and the biota in it, one of which is macrozoobenthos Macrozoobenthos can be used for public consumption and as a bioindicator of water quality. Research in several locations that represent the conditions on the island needs to be carried out to determine the state of the seagrass ecosystem and the presence of macrozoobenthos around the residential islands. Choosing the representative location for each island is used a purposive sampling technique. With this research, it is hoped that it can provide information input to interested parties in the Thousand Islands National Park area, especially in managing resource conservation and public outreach. The study results show that seagrass density is in moderate to dense conditions, as for the quality of the waters in a mild and good conditions. The statistical test results show a positive correlation between seagrass density and macrozoobenthos abundance. For this reason, it is necessary to increase awareness efforts for the community and interested parties in the Thousand Islands to be more concerned and maintain the existence of the remaining seagrass ecosystems.